The Effect of EFL Teacher Apprehension and Teacher Burnout on Learners’ Academic Achievement - Wang, Zhiping (Frontiers in Psychology, 2022)
This review aims at investigating the related studies on the role of teacher burnout and teacher apprehension in learners’ academic achievement. The negative effect of teacher burnout on learners’ academic achievement has been corroborated in the review of the literature. Furthermore, the effect of teacher apprehension on learners’ academic success has not been widely studied. However, some stressors such as having insufficient L2 knowledge, cultural differences, and classroom management problems can affect learners’ academic achievements. Finally, the pedagogical implications are illuminated for teachers, administrators, researchers, managers, teacher trainers, and counselors to decrease teacher burnout and apprehension and to develop language teaching quality in the language educational system. Some suggestions for further research are also provided to expand the current literature on teacher burnout and apprehension in English as a Foreign Language (EFL) contexts.